1993
DOI: 10.1021/bp00024a014
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Carbon Dioxide Measurement and Its Correlation with Operating Parameters in Fermentation Processes

Abstract: A silicone tubing probe was used to measure dissolved carbon dioxide in two industrial fermentation processes. The two processes differed markedly in their broth viscosities: one had high viscosity (2000-3000 cP) and the other had low viscosity (< 100 cP). The goal was to study changes in dissolved carbon dioxide concentration in fermentation broth when operating parameters, such as total pressure, air flow rate and, agitation rate, were modified. It was shown that in high-viscosity fermentation broths the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
5
12
0
Order By: Relevance
“…pCO 2 in the liquid phase is assumed to be in equilibrium to the gas phase CO 2 according to Henry’s law in an ideally mixed tank because the limiting step in gas exchange is the diffusion of CO 2 in the liquid phase. Results from literature confirm this, at least for non-viscous culture broths where gas diffusion is not hindered [15,16]. …”
Section: Resultssupporting
confidence: 59%
“…pCO 2 in the liquid phase is assumed to be in equilibrium to the gas phase CO 2 according to Henry’s law in an ideally mixed tank because the limiting step in gas exchange is the diffusion of CO 2 in the liquid phase. Results from literature confirm this, at least for non-viscous culture broths where gas diffusion is not hindered [15,16]. …”
Section: Resultssupporting
confidence: 59%
“…Only in some cases pCO 2 has been measured in the exhaust gas. This is important since there exists a complex relationship between dCO 2 and CO 2 in the gas phase that cannot be easily predicted, as both variables can constantly vary in a culture due to changes in specific and overall oxygen uptake rate, as well as operational changes in gas flow rate, agitation rate, and total pressure, among others (Dahod 1993;El-Sabbagh et al, 2006;McIntyre and McNeil, 1997). To overcome the limitations of studies reported to date, in the present work the effect of CO 2 was determined in batch cultures of recombinant E. coli by continuously measuring dCO 2 online and controlling it at constant values.…”
Section: Introductionmentioning
confidence: 99%
“…Aeration provides oxygen as well as strips CO 2 and often ammonia (Roman and Gavrilescu,1994), eliminating two potential inhibitors of secondary metabolism. Production rate suppression has been caused specifically by dCO 2 levels rising above a threshold value (Dahod,1993). For example, there was a linear streptomycin titer decline at 140 h for dCO 2 levels above 8 mL/100 mL within the first 50 h of fermentation (Bylinkina and Birukov,1972).…”
Section: Resultsmentioning
confidence: 99%